2006
DOI: 10.1007/s10531-005-0605-y
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Vertebrate Fauna in the Remote and Pristine Sub-Antarctic Cape Horn Archipelago, Chile

Abstract: Pristine wilderness is a scarce global resource, but exotic species are so common that they constitute a principal component of worldwide ecological change. The relationship between these two topics, invasion and remoteness, was the impetus behind five years of fieldwork aimed at identifying the assemblage and range of exotic vertebrates in Cape Horn, Chile, identified as one of the world's most pristine wilderness areas. While the archipelago has extremely low human population density and vast tracts of undis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0
17

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 8 publications
3
67
0
17
Order By: Relevance
“…Domestic animals can impact native fauna in several ways, including increased predation (Lepczyk et al, 2004;Kays and DeWan, 2004), especially on islands (Burbidge, 1999;Anderson et al, 2006), and genetic introgression (Vilà and Wayne, 1999;Adams et al, 2003), which sometimes might disturb the genetic integrity of native species (Pierpaoli et al, 2003). Disease transmission seems, however, to be the most important disturbance effect in many continental countries (Cleaveland et al, 2000;Frolich et al, 2000;Anderson et al, 2003;Hammer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domestic animals can impact native fauna in several ways, including increased predation (Lepczyk et al, 2004;Kays and DeWan, 2004), especially on islands (Burbidge, 1999;Anderson et al, 2006), and genetic introgression (Vilà and Wayne, 1999;Adams et al, 2003), which sometimes might disturb the genetic integrity of native species (Pierpaoli et al, 2003). Disease transmission seems, however, to be the most important disturbance effect in many continental countries (Cleaveland et al, 2000;Frolich et al, 2000;Anderson et al, 2003;Hammer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Disease transmission seems, however, to be the most important disturbance effect in many continental countries (Cleaveland et al, 2000;Frolich et al, 2000;Anderson et al, 2003;Hammer et al, 2004). Past studies have explored the presence of domestic dogs in wild areas or their impact on wild species (Herranz et al, 2002;Butler et al, 2004;Manor and Saltz, 2004;Anderson et al, 2006), however few studies have been conducted in Neotropical forests. These include predation on native species (Kruuk and Snell, 1981;Barnett and Rudd, 1983), potential disease transmission (Ryan et al, 2003;Fiorello et al, 2004;Deem and Emmons, 2005;McFadden et al, 2005;Fiorello et al, 2006), and social biology of free-roaming dogs (Daniels and Bekoff, 1989;Fielding and Mather, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Dogs can prey upon other mammals, mainly C. paca, M. gouazoubira, and D. azarae. Several authors showed that the presence of dogs in forests can lead to the decline of native species, causing a negative environmental impact (Horowitz, 1992;Lacerda et al, 2009;Oliveira and Cavalcanti, 2002;Butler et al, 2004;Anderson et al, 2006;Galetti and Sazima, 2006;Srbek-Araújo and Chiarello, 2008). Torres and Prado (2010) concluded that by increasing the awareness of residents in the surroundings of a forest is crucial to reduce the impacts of domestic dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Pets can also affect the native fauna in several ways, including increase in predation (Kruuk and Snell, 1981;Barnett and Rudd, 1983;Lepczyk et al, 2004;Kays and Dewan, 2004) and disease transmission (Anderson et al, 2006;Hammer et al, 2004). Galetti and Sazima (2006) stated that the high impact of feral dogs on some mammals is probably the major cause of extinction in their study area (Santa Genebra Forest, southeastern Brazil).…”
Section: Introductionmentioning
confidence: 99%
“…Hasta la fecha, no se han confirmado registros en algunos lugares remotos del archipiélago, como la Isla de los Estados (Argentina) y el Archipiélago Wollaston que constituye el Parque Nacional Cabo de Hornos (Anderson et al 2006;Valenzuela et al 2014 En este contexto, las imágenes satelitales resultan útiles para el estudio de distribución del castor en lugares remotos o difícil acceso. A partir de un reconocimiento visual de castoreras en imágenes de alta resolución espacial disponibles en Google Earth® (http://earth.google.com), se realizaron recorridos (transectas) en sentido Este-Oeste en toda la Reserva de Biosfera Cabo de Hornos (RBCH), a 1 km de "altura visual o de Ojo".…”
unclassified